2022
DOI: 10.1063/5.0106724
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and simulation of small cryogenic neon pellet Ne-I 640 nm photon efficiency during ablation in DIII-D plasma

Abstract: Small (∼1 mm) neon pellet fragments are fired into DIII-D H-mode plasmas, and resulting trajectory-averaged photon efficiencies (neutral neon ionization events for every photon emitted) of [Formula: see text] are estimated for Ne-I 640 nm by dividing the estimated initial pellet fragment mass by the measured number of emitted Ne-I photons. The experiments are modeled by running the Lagrangian particle (LP) fluid/magneto-hydrodynamic pellet code to estimate axial ablation plume neon density profiles and tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Initially, this model was built for interpreting the spectrum of the ablation cloud of a pellet injected in the LHD (shown in figure 3 of [12]). Starting from the fact that the emission lines of neutral Hydrogen exhibit Stark broadening profiles, the electron density was evaluated through comparison with theoretical data, with a high enough value for justifying complete Local Thermodynamic Equilibrium (LTE) in the cloud (this still remains an approximation, as demonstrated in [17], its importance must be determined and taken into account during the analysis of the results). It was also demonstrated that the continuum radiation is dominated by two components, which correspond to radiative recombination and radiative electron attachment, respectively.…”
Section: Emission Modelmentioning
confidence: 99%
“…Initially, this model was built for interpreting the spectrum of the ablation cloud of a pellet injected in the LHD (shown in figure 3 of [12]). Starting from the fact that the emission lines of neutral Hydrogen exhibit Stark broadening profiles, the electron density was evaluated through comparison with theoretical data, with a high enough value for justifying complete Local Thermodynamic Equilibrium (LTE) in the cloud (this still remains an approximation, as demonstrated in [17], its importance must be determined and taken into account during the analysis of the results). It was also demonstrated that the continuum radiation is dominated by two components, which correspond to radiative recombination and radiative electron attachment, respectively.…”
Section: Emission Modelmentioning
confidence: 99%